LEARNING EFFECTIVENESS OF DISCOVERY LEARNING MODEL BASED ON LOCAL WISDOM TO IMPROVE COMMUNICATION ABILITY AND SELF EFFICACY OF UPMI MEDAN STUDENTS IN ECONOMIC MATHEMATICS COURSE - Nova Riani; Winanda Marito; Rizka Fahruza Siregar; Rini Ramadhani; Hetty Elfina (Jurnal Scientia, 2022)
The purpose of this study was to see the effectiveness of the Discovery Learning learning model based on local wisdom, the differences in communication skills and self-efficacy of students who were taught using the local wisdom-based Discovery Learning learning model with those taught using conventional learning. This study also aims to find out how to increase students' communication skills and self-efficacy when taught using the Discovery Learning method based on local and conventional wisdom. This research method is quasi-experimental with Posttest Only Control Group Design with descriptive analysis used to achieve this goal. This research was conducted at UPMI Medan. The population of this study were all students of UPMI, while the sample was students of the Department of Management. This study found that the Discovery Learning learning model based on local wisdom was effectively used with a percentage of learning implementation worth 94.12% and student responses 89.50%. then there are differences in communication skills and self-efficacy between experimental and control class students, as evidenced by the sig. (2-tailed) 0.000005 between the control and experimental groups. This study also found a greater increase in communication skills and self-efficacy of students who were taught using Discovery Learning based on local wisdom than conventional learning, as seen from the average scores of 76.12 (experimental group) and 58.00 (control group), indicating an increase of 12 0.04%.